Lipidomics of microalgae: unraveling their lipid signature and bioprospecting bioactive phytochemicals - Couto, Daniela Salomé Moderno do (2023)
Microalgae have increasingly attracted the attention of consumers because they are rich in essential nutrients, such as omega-3 and omega-6 lipids, and their consumption has been described as beneficial to human and animal health. However, the majority of the published works on the lipid characterization of microalgae, described the identification of fatty acids profile, and other abundant and bioactive lipids such as phospholipids and glycolipids are little known. Thus, this thesis had the objectives of identifying and comparing the polar lipid and fatty acid profiles of industrially cultivated microalgae with added value, using modern lipidomic approaches based on mass spectrometry and evaluating their biological activities. The specific goals were to (1) Identify the lipidome of the microalgae C. vulgaris grown under autotrophic and heterotrophic conditions (designated respectively C-Auto and C-Hetero); (2) Identify the lipid profile of C-Auto and C-Hetero extracts extracted with a solvent and technology allowed in the food industry (ethanol and ethanol assisted by ultrasound probe), used as alternative methods to traditional extraction methods; (3) Identify the lipid composition of extracts of 2 new strains of C. vulgaris developed by chemically-induced random mutagenesis, and cultured heterotrophically. These new strains are approved as a food supplement and food ingredient (herein designated as C-White and C-Honey); (4) Identify the lipid profile of 2 species of Nannochloropsis (N. oceanica and N. limnetica) and evaluate their plasticity with growing conditions (indoors and outdoors); (5) Compare the polar lipidome of 7 species of microalgae belonging to 3 different phyla, Chlorophyta (C. vulgaris, S. obliquus, T. chuii, C. amblystomatis), Ochrophyta (N. oceanica, P. tricornutum) and Cyanobacteria (Spirulina sp) and evaluate the chemotaxonomic potential of the microalgae polar lipids; (6) Evaluate in chemico the antioxidant properties of lipid extracts from the 2 Nannochloropsis and the 4 C. vulgaris strains and the anti-inflammatory properties of the 4 C. vulgaris strains. (7) Evaluate in vitro the anti-inflammatory activity of lipid extract and fractions enriched in phospholipids and glycolipids from N. oceanica. The results obtained in the study of the lipidome of C. vulgaris grown in autotrophy and heterotrophy allowed to identify the profile of phospholipids and glycolipids of these algae and showed that the autotrophic growth of C. vulgaris induced an increase in the production of glycolipids and lipid species esterified with more unsaturated fatty acids, namely ALA. On the other hand, the heterotrophic growth increased the content of phospholipids and lipid species with less unsaturated fatty acids, namely LA. The lipid composition of the C-Auto and C-Hetero extracts extracted with ethanol and ultrasounds probe was similar to the lipid composition of the extracts extracted with the conventional dichloromethane/methanol method, so these UAE ethanol extracts can be used in the future as ingredients in new food products. The lipidome analysis of the C-White and C-Honey indicates that the lipidome of these algae includes the same lipid classes as C-Hetero, except for 3 lipid classes only identified in these new strains (DGGA, PS and CL). In addition to these classes, it was also observed significant differences in the relative abundance of most lipid species identified (~80 %) in both strains, revealing a strain-specific lipid signature. The lipid signature of N. oceanica and N. limnetica were also evaluated using modern lipidomics approaches. The results obtained showed that N. Oceanica is richer in some betaine lipids and less rich in lysolipids compared to N. limnetica. It also was found that growth conditions influence the lipid composition, by modulating the abundance of some lipid species. Both species grown outdoors were richer in phospholipids and betaine lipids esterified with EPA, but when grown indoors their lipid content increased, particularly of glycolipids. After lipid identification of the selected algae, a comparison of their lipidome was performed to assess similarities and differences and whether this lipid signature had any correlation with taxonomic classification. Lipidomic analysis of the 7 commercialized microalgae species allowed the identification of a total of 19 lipid classes, from phospholipid, glycolipid, betaine, and sphingolipid, but only 12 classes were common in all algae. Lipidomic analysis and statistical analysis of the data revealed a species-specific lipid signature of the microalgae. However, some characteristics of the lipidome were observed that allowed the classifying of the algae by phylum and marine or freshwater environments. Glycolipids were the most conserved group of lipids of microalgae belonging to the same phylum. On the other hand, betaine lipids and EPA-esterified lipids were the most abundant lipids in marine microalgae, while the lipidome of freshwater microalgae was characterized by a higher amount of lipids esterified with ALA. Regarding the bioprospecting of the lipid extracts, it was found that all the extracts had antioxidant potential measured by DPPH● and ABTS●⁺ radical scavenging activities, with C-Auto and C-Hetero having the highest antioxidant potential. As for the Cox-2 inhibition potential, C-Auto and C-Hetero also showed higher anti-inflammatory activity. It was also observed that the antioxidant activity of C-Auto and C-Hetero extracts extracted with ethanol and ultrasound, was similar to extracts obtained with conventional methods using chlorinated solvents. Both N. oceanica total lipid extract and fractions showed anti-inflammatory potential by decreasing NO levels and expression of proinflammatory genes in LPS-stimulated macrophages. Thus, this work allowed the identification, for the first time, of the lipidome of microalgae with industrial application, showing that the lipidome is species-specific, although we could observe some characteristics which were typical of the phylum or the environment (freshwater or saltwater species). It was also shown that the lipidome can be modulated by growth conditions, and that lipid extracts have bioactive properties, namely antioxidant and anti-inflammatory properties. These results may contribute to the development of new microalgae-based products for application in the food, nutraceutical or supplement industries, among others.